2006
DOI: 10.1007/s10498-006-9009-1
|View full text |Cite
|
Sign up to set email alerts
|

Dissolved rare earth elements in river waters draining karst terrains in Guizhou Province, China

Abstract: Winter seasonal concentrations of dissolved rare earth elements (REE) of two major river systems (the Wujiang River system and the Yuanjiang River system) in karst-dominated regions in winter were measured by using a method involving solvent extraction and back-extraction and subsequent ICP-MS measurements. The dissolved REE concentrations in the rivers and their tributaries are lower than those in most of the large rivers in the world. High pH and high cation (i.e., Na + + Ca 2+ ) concentrations of the rivers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
27
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 51 publications
(28 citation statements)
references
References 28 publications
0
27
0
1
Order By: Relevance
“…We hence used the method of Shabani et al (1990) to increase the concentration of the REE by at least a factor of 100. The procedure of determining the concentrations of dissolved load REE is similar to that described by Han and Liu (2007). The preconcentration of dissolved load REE concentration involves the following steps: REE were extracted from water samples with 65% HDEHP (2-ethylhexyl hydrogen phosphate) and 35% H 2 MEHP (2-ethylhexyl dihydrogen phosphate) in heptane, then back-extracted with 6 N ultra-purified hydrochloric acid and transformed into nitrates of REE for ICP-MS analysis.…”
Section: Sampling Strategies and Analytical Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We hence used the method of Shabani et al (1990) to increase the concentration of the REE by at least a factor of 100. The procedure of determining the concentrations of dissolved load REE is similar to that described by Han and Liu (2007). The preconcentration of dissolved load REE concentration involves the following steps: REE were extracted from water samples with 65% HDEHP (2-ethylhexyl hydrogen phosphate) and 35% H 2 MEHP (2-ethylhexyl dihydrogen phosphate) in heptane, then back-extracted with 6 N ultra-purified hydrochloric acid and transformed into nitrates of REE for ICP-MS analysis.…”
Section: Sampling Strategies and Analytical Methodsmentioning
confidence: 99%
“…In Han and Liu (2007), the authors investigated the dissolved REE in river waters in Guizhou Province, China. They did not, however, get sufficient SPM in the low-flow season.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding REE migration, some studies have shown that REE are immobile during surface processes (Szczepanski and Ilnicki, 2014). However, some researchers have found that the mobility of REE was controlled by pH values (Han et al, 2009;Pazand and Javanshir, 2014) and REE was generally believed to be mobile at a lower pH value (Han and Liu, 2007;Migaszewski et al, 2014). However, there is In karst regions of the Southwest (SW) China, the degradation of ecosystems has led to many ecological problems, such as Karst Rocky Desertification.…”
Section: Introductionmentioning
confidence: 99%
“…Their use as proxies is applied in different disciplines of the earth sciences, especially hydrology, geochemistry, and geology (Aubert et al, 2004;Egashira et al, 1997;Han and Liu, 2006;Henderson, 1984;Hu et al, 2006;Li et al, 1998;Protano and Riccobono, 2002;Tyler, 2004;Wang et al, 2004).…”
mentioning
confidence: 99%
“…Until recently, little information had been available for estimating the environmental and ecological impacts of REEs, and such information was generally scarce and sometimes contradictory (Aubert et al, 2004;Chen, 1993;Egashira et al, 1997;Han and Liu, 2006;Henderson, 1984;Hu et al, 2006;Li et al, 1998;Markert and Zhang, 1991;Wang, 1991a,b;Wang et al, 2004). Therefore, it is important to obtain more knowledge about the different environmental effects of REEs to predict possible deleterious effects.…”
mentioning
confidence: 99%